BIRDS, BEASTS, AND NATURE: AN ECOLINGUISTIC AND AXIOLOGICAL STUDY OF METAPHOR SOURCE DOMAINS IN ENGLISH AND UZBEK PROVERBS - Axmedov, Ikboljon (QO‘QON UNIVERSITETI XABARNOMASI, 2025)
This study investigates animal- and nature-based metaphorical source domains in English and Uzbek proverbs to reveal the ecological and axiological beliefs encoded in folk wisdom. Using a purposive corpus of 240 proverbs (120 English, 120 Uzbek) selected from proverb dictionaries, academic collections and national folklore archives, the paper applies Conceptual Metaphor Theory and an ecolinguistic/axiological interpretive framework to (1) identify recurring animal and natural source domains, (2) classify axiological (value) loadings attached to those domains (positive, negative, ambivalent), and (3) compare cross-cultural similarities and differences. Results show strong overlap in animal metaphors (dog, fox, wolf, sheep, horse, lion) but culture-specific mappings too (camel, steppe/desert imagery in Uzbek proverbs; lion/kingly imagery in English). Uzbek proverbs display pronounced ecological embedding — values emphasizing endurance, communal harmony, and contextual prudence — while English proverbs reflect individual-centered moral evaluations alongside animal trait metaphors. The findings demonstrate how proverb metaphors act as cultural-ecological memory, preserving long-standing human–nature relations and moral priorities.